1996
DOI: 10.1111/j.1600-0447.1996.tb09851.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of mood and behaviour in a healthy middle‐aged population in Japan

Abstract: A population survey of seasonality in six representative cities in Japan was conducted using the Japanese version of the Seasonal Pattern Assessment Questionnaire (SPAQ). The questionnaires were given to 951 parents (male: female ratio 1:1 age range 34-59 years) of high-school students. Significant regional differences in seasonal variations of mood, length of sleep, and weight were observed; the proportion of individuals reporting high seasonality in the two northern cities was significantly higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 14 publications
4
37
2
3
Order By: Relevance
“…Not only climatic differences, but also population differences might account for the results. Thus, Ozaki et al (1995), in a Japanese study of seasonal variations in mood (Nagoya, latitude 35°N), and Han et al (2000), in a Chinese study (Jining, latitude 35°N), obtained results that were in contrast to those from most studies of Caucasian populations (Rosenthal et al 1984), with a greater frequency of summer versus winter mood Okawa et al (1996) showed significant regional differences in seasonal changes in mood in Japan. Subjects living in the northern part of Japan reported "feeling worse" in winter and those living in the south felt worse in summer.…”
Section: Acth and Cortisolmentioning
confidence: 79%
“…Not only climatic differences, but also population differences might account for the results. Thus, Ozaki et al (1995), in a Japanese study of seasonal variations in mood (Nagoya, latitude 35°N), and Han et al (2000), in a Chinese study (Jining, latitude 35°N), obtained results that were in contrast to those from most studies of Caucasian populations (Rosenthal et al 1984), with a greater frequency of summer versus winter mood Okawa et al (1996) showed significant regional differences in seasonal changes in mood in Japan. Subjects living in the northern part of Japan reported "feeling worse" in winter and those living in the south felt worse in summer.…”
Section: Acth and Cortisolmentioning
confidence: 79%
“…Also, Morrissey et al (1996) showed changes in mood during the summer in the tropical climate of Australia (relative humidity 69.5%), suggesting that a combination of raised heat and humidity affected mood. Other investigators have reported seasonal variations in the incidence of suicide, with higher rates in the warmer months (Preti and Miotto 2000), and a greater frequency of mood disorders during the summer in the Japanese population (Ozaki et al 1995;Okawa et al 1996). In our previous study (Kanikowska et al 2009), we observed significant seasonal differences in the POMS subscales Anger-Hostility (A-H) and Tension-Anxiety (T-A), with higher scores in spring, as well as higher concentrations of adrenocorticotrophic hormone (ACTH) and catecholamine metabolites in summer.…”
Section: Discussionmentioning
confidence: 97%
“…Da aber möglicherweise ein exogener Lichtmangel die Manifestation einer SAD triggert [9,10,43], wurden schon früh Untersuchungen über die Prävalenz und klinische Ausprägung in unterschiedlichen geographischen Regionen und Populationen durchgeführt [4,7,11,20,29,30,31,32,45,53]. In Nordamerika wurde dabei eine Zunahme der Prävalenz für SAD und s-SAD vom Wintertyp mit nördlicher Breite gefunden [37].…”
Section: Schlüsselwörterunclassified
“…Das von uns gefundene Geschlechtsverhältnis von Frauen:Män-ner=3,4:1 deckt sich weitgehend mit Ergebnissen aus vorangehenden Untersuchungen in Europa [50,55], Nordamerika [5,48] und Australien [6], in denen Werte von 3,5:1 bis 9:1 gefunden wurden. Lediglich in Asien scheint das Geschlechtsverhältnis mit 1,2:1 bis 1,9:1 niedriger zu sein [32,42,46].Wie bereits zuvor berichtet [52], war auch bei uns die Geschlechtsdifferenz bei Patienten mit bipolar affektiver Störung geringer ausgeprägt als bei unipolar Depressiven (bei uns 1,5:1 bzw. 5.0:1).…”
Section: Diskussionunclassified